Efficacy of mesenchymal stem cell-delivery using perpendicular multi-needle injections to the skin: Evaluation of post-ejection cellular health and dermal delivery. Issue 3 (May 2023) - Rangatchew, Filip; Rasmussen, Bo Sonnich; Svalgaard, Jesper Dyrendom; Haastrup, Eva; Talman, Maj-Lis M.; Bonde, Christian; Fischer-Nielsen, Anne; Drzewiecki, Krzysztof T.; Holmgaard, Rikke; Munthe-Fog, Lea
Abstract: Aim: Mesenchymal stem cell (MSC)-therapy is increasingly being evaluated in clinical trials. Dermal delivery is not only time consuming but also unreliable, potentially hampering the therapeutic result. Therefore, qualification of cell delivery protocols is essential. This study evaluated a clinically relevant automated multi-needle injection method for cutaneous MSC-therapy, allowing the skin to be readily and timely treated, by assessing both the cellular health post-ejection and dermal delivery. Methods: Following dispensation through the injector (31 G needles: 9- or 5-pin) the cellular health and potency (perceived- and long-term (12 h) viability, recovery, metabolism, adherence, proliferation and IDO1-expression) of adipose-derived stem cells (10–20–50 ×10 6 cells/ml) were assessed in vitro in addition to dermal delivery of solution in human skin. Results: No significant detrimental effect on the perceived cell viability, recovery, metabolism, adherence or IDO1-expression of either cell concentration was observed. However, the overall long-term viability and proliferation decreased significantly regardless of cell concentration, nonetheless marginally. An injection depth above 1.0 mm resulted in all needles piercing the skin with dermal delivery from up to 89% needles and minimal reflux to the skin surface, and the results were confirmed by ultrasound and histology. Conclusion: The automated injector is capable of delivering dermal cell-doses with an acceptable cell quality. Highlights: Qualification of cell delivery protocols is crucial to ensure reproducible therapies. The study validates a clinically relevant injection method for cutaneous MSC-therapy. The method reliably delivers dermal doses with an acceptable cell viability. The method allows for the skin to be readily treated with MSC in a timely manner.